2012
DOI: 10.1016/j.clim.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulatory function in circulating CD4+CD25highCD127low/− T cells in patients with myasthenia gravis

Abstract: Previous studies have reported alterations in numbers or function of regulatory T cells (Tregs) in myasthenia gravis (MG) patients, but published results have been inconsistent, likely due to the isolation of heterogenous “Treg” populations. In this study, we used surface CD4, CD25high, and CD127low/− expression to isolate a relatively pure population of Tregs, and established that there was no alteration in the relative numbers of Tregs within the peripheral T cell pool in MG patients. In vitro proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 54 publications
13
98
1
Order By: Relevance
“…CD4 + CD25 + FoxP3 + regulatory T cells have a key role in controlling autoimmunity and maintaining immunologic selftolerance [105]. Recent studies have reported functional defects of CD4 + CD25 + regulatory T cells from thymuses of MG patients and reduction in peripheral regulatory T cell population in untreated MG patients [106][107][108][109][110][111][112]. Impairment of suppressive activity of regulatory T cells and reduction in frequency of regulatory T cells in the spleen and peripheral blood were also demonstrated in EAMG rats [113,114].…”
Section: Mechanisms Of Specific Immunotherapymentioning
confidence: 84%
“…CD4 + CD25 + FoxP3 + regulatory T cells have a key role in controlling autoimmunity and maintaining immunologic selftolerance [105]. Recent studies have reported functional defects of CD4 + CD25 + regulatory T cells from thymuses of MG patients and reduction in peripheral regulatory T cell population in untreated MG patients [106][107][108][109][110][111][112]. Impairment of suppressive activity of regulatory T cells and reduction in frequency of regulatory T cells in the spleen and peripheral blood were also demonstrated in EAMG rats [113,114].…”
Section: Mechanisms Of Specific Immunotherapymentioning
confidence: 84%
“…An extension of these observations is that defects in Treg number or function may underlie the development of human autoimmune disorders. Importantly, Tregs have been implicated in preventing autoantibody production by self-reactive B cells [75][76][77], and dysfunction or deficiencies of Tregs have been demonstrated in MG [63,[78][79][80][81].…”
Section: T-cell Signaling Pathways and Tregsmentioning
confidence: 99%
“…Multiple sclerosis, psoriasis, Type I diabetes and also AChR-MG patients show a significant decrease in the suppressive function of Tregs compared with HC [10,[67][68][69]. This section focuses on discussing the several studies that have been undertaken on characteristic, quantitative and qualitative changes of Tregs in MG patients.…”
Section: Studies Of Tregs In Patients With Mgmentioning
confidence: 98%
“…Several studies have demonstrated that Tregs from AChR-MG have a severe defect in their suppressive function, suggesting a role for Tregs abnormalities in MG pathogenesis [10][11][12]. Once T/B cells are activated, one could expect their activation status to be regulated by Tregs; but, since AChR-MG Tregs are dysfunctional, they cannot suppress the pathological responses of those cells that lead to the high level of autoreactive cells, which can extend inflammation and autoimmunity.…”
mentioning
confidence: 99%